The Race to Find COVID-19 Vaccine: So Near, Yet so Far! - Sonali Sachdeva; Udita Gupta; Anupam Prakash; Shubha Laxmi Margekar; Ritika Sud (Indian Journal of Medical Specialities)
In a brief span of time, coronavirus has become a major cause of concern worldwide ever since the first case was reported in Wuhan, China in December 2019. The pace at which the virus is being transmitted across the globe and the sudden increase in numbers of cases is much faster than severe acute respiratory syndrome and Middle East respiratory syndrome. With the rising number of cases, coronavirus disease 2019 (COVID-19) not only has an adverse effect on health, it has a deep seated impact on the economic and social front. Hence, the development of an effective vaccination strategy seems to be the only light at the end of the tunnel. The ongoing pandemic mandates the speedy evaluation of multiple approaches in order to elicit protective immunity and to curtail unwanted immune-potentiation which plays an important role in the pathogenesis of this virus. Being developed by more than 90 institutions in the world, a vaccine which is both effective and safe becomes all the more essential in the current time. Various types of vaccine strategies are being tested under different phases of clinical trials. The present paper hopes to provide an overview of the current work going on in this direction, with an aim to further fuel effects for an early and effective COVID-19 vaccine platform.